Answer:
See below ~
Step-by-step explanation:
[tex]\textsf {Each of the steps has been reasoned below :}[/tex]
[tex]\implies \textsf {3x - 2 = 4 (Given)}[/tex]
[tex]\implies \textsf {3x = 6 (Addition Property of Equality)}[/tex]
[tex]\implies \textsf {x = 2 (Division Property of Equality)}[/tex]
[tex]\textsf {In the second step, the property has been applied}\\\textsf {by adding 2 to each side of the equation.}[/tex]
[tex]\textsf {In the third step, the property has been applied by dividing 3 on each side.}[/tex]